BREAKING THE CYCLE OF POVERTY FOR CHILDREN THROUGH SOCIAL SUPPORT AND EDUCATION IN ROMANIA - Golai Vînătoru, Nicoleta; Nițu, Anemari Helen (International Journal of Child, Youth and Family Studies, 2025)
In Romania in 2024, 33.9% of children faced poverty and social exclusion, the third highest rate in the EU. Despite the European Child Guarantee’s initiatives, public resources remain insufficient to meet the needs of vulnerable children. Non-governmental organizations (NGOs), such as our own CONCORDIA Humanitarian Organization, play a crucial role in addressing these gaps through multidisciplinary interventions. CONCORDIA’s Day Center model offers essential services to improve school retention and reduce family abandonment, including educational support, social assistance, and medical care. Recognizing the need for systemic impact, CONCORDIA launched CentreZi RO, a national network of Day Centers, to foster collaboration among service providers and advocate for policy improvements. However, the existing 860 centers are far from sufficient, with an estimated 3,000 more required nationwide. To sustainably expand its reach, CONCORDIA has introduced a social franchise model, enabling the structured replication of its intervention strategy while maintaining service quality. This model prioritizes child participation, family engagement, and community empowerment, aligning with the Lundy Model of Child Participation. Strengthening public–private partnerships and increasing investment in social services are essential for breaking the cycle of intergenerational poverty. Through integrated social and educational interventions, CONCORDIA demonstrates a scalable solution for reducing child poverty and fostering long-term systemic change.